Efficient oxidative cyclisation of acid hydrazides to 2, 5-disubstituted 1, 3, 4-oxadiazoles catalysed by Bu4NI with t-BuOOH as oxidant. (1st August 2013) - Gao, Peng; Wei, Yunyang
Acid hydrazides or araldehyde N-acylhydrazones can be converted in good yields to, respectively, symmetrical or unsymmetrical, 2, 5-disubstituted 1, 3, 4-oxadiazoles at 60 °C by a Bu4NI-catalysed procedure which requires the presence of a base and 2.5 equiv. of t-butyl hydroperoxide.